2020
DOI: 10.1016/j.trip.2020.100218
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown and reduction of traffic accidents in Tarragona province, Spain

Abstract: This paper analyses the impact that the lockdown decreed by the Spanish Government to combat the spread of COVID-19 has had on traffic accidents in Tarragona province (Spain). During the studied period of the lockdown (March 16 - April 26 2020) the number of accidents per day fell by 74,3% in coparison with those in February 14-20 (reference week) and 76% in respect to the equivalent period in 2018-2019. This reduction of accidents has been higher than the decrease of mobility during the same reference period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 49 publications
(53 reference statements)
6
109
0
6
Order By: Relevance
“…They also found an overall reduction in accidents (41%), with early morning crashes (0:00–5:00 AM) having the largest reduction (81%). Saladie et al (2020) found similarly large reductions in accidents (74% compared to February of 2020; 76% compared to 2019) attributable to overall reductions in travel volume (nearly 63%) in Tarragona Province, Spain. Colonna and Intini (2020) found that overall reduced mortality from traffic accidents was compensated by increased deaths due to the pandemic.…”
Section: Short-term Impactsmentioning
confidence: 85%
“…They also found an overall reduction in accidents (41%), with early morning crashes (0:00–5:00 AM) having the largest reduction (81%). Saladie et al (2020) found similarly large reductions in accidents (74% compared to February of 2020; 76% compared to 2019) attributable to overall reductions in travel volume (nearly 63%) in Tarragona Province, Spain. Colonna and Intini (2020) found that overall reduced mortality from traffic accidents was compensated by increased deaths due to the pandemic.…”
Section: Short-term Impactsmentioning
confidence: 85%
“…While there is consensus on a reduction in collisions, [15][16][17][18] the results on fatalities are not always in the same direction. 2,19 Findings also provide additional evidence on the spillover effects of Covid-19 on other health outcomes in Northern Ireland and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Early empirical evidence suggests that there has been a decrease in collisions during the pandemic. 2,[15][16][17][18] Interestingly, in the USA there has been a reduction in MVCs in the first months of the Covid-19 pandemic, [15][16] but at the same time there has been an increase in deaths. 19 The objective of this study is to examine whether and to what extent MVCs, injuries and deaths were affected by the Covid-19 pandemic in Northern Ireland.…”
Section: Introductionmentioning
confidence: 99%
“… de Haas et al (2020) reported that under the Dutch ‘intelligent lockdown’ policy, there was also a reduction in outing behavior of about 80%. Saladié et al (2020) reported a 62.9% reduction in behavior and a related 74.3% reduction in traffic accidents in Tarragona province in Spain, where lockdown was implemented. Thus, under the lock down policy, people reportedly reduced most of their movement behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%